Dumbo - Walt Disney Company; Aberson, Helen; Perl, Harold; Walt Disney Company (United States of America : Rollabooks, 1996)
A little elephant uses his enormous ears to become the star of the circus.
Keywords: Elephants -- Fiction; Circus -- Fiction